makna simbolik beluk dalam tradisi masyarakat sunda: pemaknaan dari simbolik tradisi 'beluk' dalam masyarakat sunda - Suhadi, Mahardiansyah; Permana, Renaldi; Permana, Satria Yuda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
Beluk is a traditional form of vocal art that thrives within the cultural life of the Sundanese people, particularly in the Priangan region of West Java, Indonesia. As an oral performance art, beluk functions not only as entertainment but also as a medium that conveys symbolic meanings reflecting the worldview, value systems, and social structure of Sundanese society. This study aims to explore the symbolic meanings embedded in the practice of beluk, including its performance elements, lyrics, vocal intonation, and the socio-cultural contexts in which it is performed. Using a qualitative approach and grounded in the theory of symbolic interactionism, this research examines how symbols within beluk are interpreted by the community, and how these meanings are constructed, maintained, and transmitted through social interaction. The findings reveal that beluk contains cultural symbols that represent values of harmony with nature, moral integrity, spirituality, and reverence for ancestors. These symbols are internalized through oral cultural transmission and play a crucial role in preserving the cultural identity of the Sundanese people. Thus, beluk serves not merely as an artistic expression, but also as a communicative vehicle for cultural values that strengthens social cohesion and the continuity of tradition within Sundanese society.